2016
DOI: 10.1111/ggi.12851
|View full text |Cite
|
Sign up to set email alerts
|

Is there an obesity paradox in the Japanese elderly population? A community‐based cohort study of 13 280 men and women

Abstract: The present study provides evidence of a conservative obesity paradox among older Japanese people, using the appropriate body mass index cut-off points for Asian populations. In particular, obese older men tend to have a lower risk of all-cause mortality. Geriatr Gerontol Int 2017; 17: 1257-1264.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
3
26
2
1
Order By: Relevance
“…15,19,20 Thus, the present study revealed differences from other studies in several respects. 13 The key result of the present studythe survivor effect of overweight or obesity in the older populationconfirmed that Korean older individuals also have a higher resistance to the adverse effects of obesity. Rather, the optimal BMI with a minimal mortality was between 27.5 and 30.0 kg/m 2 for men, and between 25.0 and 27.5 kg/m 2 for women.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…15,19,20 Thus, the present study revealed differences from other studies in several respects. 13 The key result of the present studythe survivor effect of overweight or obesity in the older populationconfirmed that Korean older individuals also have a higher resistance to the adverse effects of obesity. Rather, the optimal BMI with a minimal mortality was between 27.5 and 30.0 kg/m 2 for men, and between 25.0 and 27.5 kg/m 2 for women.…”
Section: Discussionsupporting
confidence: 70%
“…[5][6][7][8][9][10][11][12][13] The purpose of the present study was to evaluate the relationship between BMI and mortality in the Korean elderly population aged >65 years. [5][6][7][8][9][10][11][12][13] The purpose of the present study was to evaluate the relationship between BMI and mortality in the Korean elderly population aged >65 years.…”
Section: Introductionmentioning
confidence: 99%
“…This finding does not correspond with earlier studies that reported a conservative obesity paradox among the elderly community [7][8][9] . The author assumed that the reason for different results according to age group was because of higher perioperative mortality in the older group compared with the younger group.…”
contrasting
confidence: 99%
“…33 Similar associations have also been found in several Asian studies. [14][15][16][34][35][36] In addition, prior research has found that stable weight status is associated with a lower mortality rate compared to weight change among older adults both in Western and Asian countries. 19 The findings of our review of studies with longer follow-up periods are consistent with these prior findings.…”
Section: Comparison Across Studiesmentioning
confidence: 99%
“…4,[7][8][9][10] Moreover, in contrast to the general population, older populations tend to exhibit a reverse J-shaped or L-shaped association between BMI and all-cause mortality [11][12][13] , which has also been found in Asian counties. 4,[14][15][16] More specifically, these studies report that underweight is an important predictor of mortality, while overweight has the lowest mortality risk in old age. This pattern of association has been referred to as the "obesity paradox. "…”
Section: Introductionmentioning
confidence: 99%